Development and Validation of the Affiliation–Interpersonal Skills Questionnaire (AIS-Q) for Culturally Responsive Science Learning in Pre-Service Elementary Teachers - Aisyah Ali; Singgih Bektiarso; Auldry Fransje Walukow; Erlia Narulita; Akhmad Kadir (Postgraduate, University of Mataram, 2025)
This study addresses the need for culturally responsive science learning in elementary teacher education by developing and empirically examining Affiliation–Interpersonal Skills (AKI), comprising affiliation motivation and interpersonal skills, within an ethnoscience learning context. Using a cross-sectional design, the study involved 50 prospective elementary teachers from a public university in Papua, Indonesia, most of whom were from disadvantaged, frontier, and outermost areas. Content validity was evaluated by five experts using the Content Validity Index, while item performance and internal consistency were examined through descriptive statistics, corrected item–total correlations, and reliability analysis. The results showed that the AKI instrument demonstrated strong content validity (most items I-CVI ≥ 0.78; S-CVI/Ave ≥ 0.90) and satisfactory reliability (subscale and total coefficients ≥ 0.70). Empirically, participants exhibited generally moderate to high affiliation motivation, reflecting a strong tendency toward collaboration and social connectedness, while interpersonal skills varied across individuals, particularly in empathic communication and conflict management. Based on these patterns, three AKI profiles were identified, indicating differentiated training needs in ethnoscience-based science learning. These findings suggest that AKI is a measurable and meaningful construct for mapping prospective teachers’ social–interpersonal readiness and for informing targeted interventions to strengthen culturally responsive science instruction.